Structural stability of a polyetheretherketone femoral component—A 3D finite element simulation - Wang, Jian-ping; Guo, Dong; Wang, Shi-hua; Yang, Yong-qiang; Li, Guoan (Clinical biomechanics (Bristol), 2019)
Because its mechanical properties are similar to cortical bones of the knee, polyetheretherketone (PEEK) material has been used to make total knee arthroplasty (TKA) components. This study investigated the PEEK femoral component deformation of a TKA system and compared the data with that of a cobalt–chromium (CoCr) component. A 3D finite element knee model was constructed using CT images of a normal subject. A knee prosthesis was installed on the model to simulate a TKA knee. The material properties of the bone were assumed linear and transverse isotropic. The femoral component was modeled using a PEEK or CoCr material. A compressive load was applied to the knee at full extension. Tibiofemoral contact stresses and femoral component deformations were analyzed. Under a 3 kN load, the maximal Von-Mises stresses in the femoral component were 14.39 MPa and 30.05 MPa for the PEEK and CoCr components, respectively. At the tibial polyethylene surface, the CoCr femoral component caused higher contact stresses (>2.2%) than the PEEK component. The deformation of the PEEK component was over 3 times larger than that of the CoCr component (0.65 × 10−3 mm vs 0.2 × 10−3 mm). The PEEK femoral component could result in lower contact stresses, but larger deformations in the TKA knee compared to the CoCr component. An increased deformation of the PEEK component indicates a reduction in its structural strength. Future investigation should examine if the reduced structural strength will affect the in-vivo component-bone interface integration and affect the component fatigue life. •The deformation of the PEEK component was over 3 times larger than that of the cobalt–chromium component.•At the poly tibial surface, the cobalt–chromium femoral component caused higher maximal contact stresses than the PEEK component.